Complex irradiation history of chondrules and matrix: a study of CR2 and some other meteorites - tables 1-6" - Trieloff, Mario; Beyersdorf-Kuis, Uta; Ott, Uli (Universität, 2023)
Excesses of cosmic-ray produced nuclei in individual components of meteorites indicate “pre-irradiation”, either in the surface region of their parent bodies (PBs) or as free-floating small particles in the early Solar System (ESS), and several cases of pre-irradiation of chondrules have been inferred in previous studies. We expand on our earlier work (Beyersdorf-Kuis et al., 2015) and report a study of cosmic-ray produced He and Ne in chondrules and “matrix” material of several CR2 and CV meteorites as well as the highly primitive, unique, carbonaceous chondrite Acfer 094. In order to avoid artifacts in the interpretation due to poorly known target element abundances in the analyzed material, we performed instrumental neutron activation analysis (INAA) on the very samples subsequently used for noble gas analysis. In accordance with previous work, no evidence for pre-irradiation was found for CV3 Allende, while for CV3 Vigarano evidence for pre-irradiation is marginal at best. Chondrules from Acfer 082 (CV) exhibit both excesses and deficits relative to matrix, which points to pre-irradiation of not only chondrules, but also matrix material. A similar case may be Renazzo (CR2), where, however, the identification is complicated by the presence of abundant pre-solar Ne-E. A large number of chondrules (ten) were studied from CR2 El Djouf 001, which yielded slightly variable, small but consistent, excesses relative to matrix, corresponding to “nominal” (i.e., irradiation by galactic cosmic rays in 4 Pi geometry) excess ages of 1 to 2 Ma. Modelling based on cosmogenic 22Ne/21Ne suggest contributions from irradiation in the parent body regolith by SCR as well as GCR, where the latter dominates. The individual contributions are difficult to quantify, but variations of the GCR component may be the major cause of the variations in nominal CRE ages. Very large excesses - corresponding to nominal excess exposure ages >30 Ma - were found in two chondrules from the solar-wind-rich CR2 NWA 852, in agreement with reports in the literature. The case shows similarity to El Djouf 001 except for the much larger size of the effects, and the situation may be common among meteorites with a regolith origin. With independent information on the CRE age, SCR and GCR parent body contributions may be disentangled, providing constraints on regolith dynamics. Reevaluating the large variations previously identified in chondrules from QUE 99177 we suggest either a very different regolith history compared to that of El Djouf 001 or, more likely, pre-irradiation in the ESS as suggested by Beyersdorf et al. (2015). The single chondrule from unique Acfer 094 that we studied has a cosmic ray exposure indistinguishable from the one we found for matrix material. (2023-12-05)
Gesehen am 19.03.2024
Keywords: Forschungsdaten; Datenbank